Estimation of Acoustic Impedance for Surfaces Delimiting the Volume of an Enclosed Space - Janusz PIECHOWICZ; Ireneusz CZAJKA (Archives of Acoustics, 2013)
Several methods can be applied for analyses of the acoustic field in enclosed rooms namely: wave propagation, geometrical or statistical analysis. The paper presents problems related to application of the boundary elements method to modelling of acoustic field parameters. Experimental and numerical studies have been combined for evaluation of acoustic impedance of the material used for the walls of a model room. The experimental studies have been carried out by implementing a multichannel measuring system inside the constructed model of an industrial room. The measuring system allowed simultaneous measurements of the source parameters – the loudspeaker membrane vibration speed, the acoustic pressure values in reception points located inside the model space as well as phase shifts between signals registered in various reception points. The numerical modelling making use of the acoustic pressure values measured inside the analyzed space allowed determination of requested parameters of the surface at the space boundary.